Detailed assessment of low-back loads may not be worth the effort: Acomparison of two methods for exposure-outcome assessment of low-back pain - Coenen, Pieter; Kingma, I.; Boot, C.; Bongers, P.; van Dieën, J. (Elsevier Ltd, 2015)
The trade-off between feasibility and accuracy of measurements of physical exposure at the workplace has often been discussed, but is unsufficiently understood. We therefore explored the effect of two low-back loading measurement tools with different accuracies on exposure estimates and their associations with low-back pain (LBP).Low-back moments of 93 workers were obtained using two methods: a moderately accurate observation-based method and a relatively more accurate video-analysis method. Group-based exposure metrics were assigned to a total of 1131 workers who reported on their LBP status during three follow-up years. The two methods were compared regarding individual and group-based moments and their predictive value for LBP.Differences between the two methods for peak moments were high at the individual level and remained substantial at group level. For cumulative moments, differences between the two methods were attenuated as random inaccuracies cancelled out. Peak moments were not predictive for LBP in any method while cumulative moments were, suggesting comparable predictive values of the two methods. While assessment of low-back load improves from investing in collecting relatively more accurate individual-based data, this does not necessarily lead to better predictive values on a group level, especially not for cumulative loads.